DISCHARGE CHARACTERISTICS OF THE MAGNETRON SYSTEM FOR SPUTTERING, DEPOSITION, AND NANOTECHNOLOGY APPLICATIONS - Andrii Breus; Oleksii Serdiuk; Vasyl Ruzaikin; Oleg Baranov (Авіаційно-космічна техніка та технологія, 2020)
Magnetron sputtering is known for years as a powerful tool for coating deposition of cutting tools and machine parts. However the experimental measurements of the magnetron discharge parameters are still necessary to provide a consumer of the magnetron system with the reliable characteristics. A voltage-current relation is the most applied characteristic of the discharge, and it is described as the power low of a type U = U0 + aIn, where U and I are the voltage drop and the discharge current, respectively, and U0 and n are constant. First part of the research is dedicated to the experiments conducted in the magnetron setup provided with the titanium cathode in a vacuum chamber filled with argon or argon-nitrogen mixture, and the constants are determined for the particular geometry of the magnetron sputtering system. The obtained results can be used to choose the operation modes for the traditional applications of the magnetron discharge such as ion cleaning and heating of the non-magnetic workpieces arranged on the cathode, as well as for the sputtering deposition of the titanium and titanium nitride coatings on the surfaces of the workpieces located above the magnetron cathode. In the next part of the research the novel application of the magnetron for production of carbon nanostructures is considered. For the purpose, a layer of expanded graphite is arranged on the magnetron cathode, and the discharge is initiated in oxygen atmosphere. It was found that for the time interval of a few hours the discharge is described as a superposition of the typical magnetron glow with arc spot generation, and the intensity of the arcs is not decreased with time. At that, the arc initiation was accompanied with the formation of clusters of the graphite cathode. The process is explained in terms of the cathode spot generation at the interaction of the arc plasma with the non-melting material. This process can be beneficial for the development of the plasma reactors for the large-scale production of the carbon species at the low gas pressures suitable for the magnetron discharge operation. Thus, the magnetron sputtering systems provided with the expanded graphite cathode can be considered as the tool to grow carbon nanospecies in the arc discharge cathode spots.